Is Audit Quality at Risk in the Covid-19 Era? The Moderating Role of Client Complexity - Thalia, Michelle; Herusetya, Antonius (Jurnal Dinamika Akuntansi dan Bisnis, 2025)
This study investigated the association between low audit quality and the tendency to issue modified audit opinions (MAO), using the proxy of non-Big Four audit firms and non-industry-specialized auditors. It also investigated the moderating effect of client complexity on the relationship between audit quality and MAO, and examines the effect of COVID-19 pandemic on these relationships. The samples were all listed firms on the Indonesia Stock Exchange, except for financial industry over a period of 2018 2020 (1,020 firm-years observations). Using panel logistic regression analyses, this study reveals that non-Big Four audit firms have a greater tendency to issue MAO, with no association between non-industry-specialized auditors and the tendency to issue MAO. This study also identifies that client complexity represents a moderator that enhances the positive correlation between non-Big Four audit firms and MAO. Lastly, no evidence found of any difference in the audit quality between pre- and during COVID-19 pandemic.